The Incidence of Dermatitis Analysis Based on Individual Characteristics of Metal Plating Workers in Sidoarjo - Abdul Hakim Zakkiy Fasya (Universitas Airlangga, 2018)
Metal plating industry using hexavalent chromium (Cr6+) for main ingredient to coat metal. Chromium when contact with the body can cause various health effects. This study were analized the individual characteristics and the incidence of dermatitis on metal plating workers in Sidoarjo. This was a qualitative descriptive study using cross sectional design. Data were collected by questionnaire, observation sheet, interview guides and diagnosis sheet. Respondents were total population by the number of 10 metal plating workers. The individual characteristics sub-variables were age, type of work, working period and use of PPE. The incidence of dermatitis in the metal plating sub-variables were skin burn, dermal necrosis, dermal edema, erythema, skin redness and itching and chrome holes ulceration. There was a strong correlation between age and the incidence of skin burn (r = 0.618), as well as the type of work to the incidence of skin redness and itching, dermal necrosis and erythema with contingency coefficient (r) of 0.632; 0.626; and 0.504. In addition working period with chrome hole, skin redness and itching and skin burn has a strong correlation with contingency coefficients (r) of 0.707; 0.626; 0.539. There is also a strong correlation between the use of PPE with dermal edema incidence (r = 0.707). Metal coating workers were suggested more careful when performing plating work and always use PPE that can minimize the contact between the skin with hexavalent chromium.